The Effect of Administrative Empowerment on the Organizational Effectiveness of Bank Employees - Saleh, Motasem; Kabalan, H. (International Journal of Engineering and Management Sciences, 2022)
This study seeks to identify the level of the impact of administrative empowerment in its dimensions on the organizational effectiveness in the banking sector in Syria. In order to verify the objectives, develop and test the validity of the hypotheses, the descriptive approach was adopted. The study found that there is a statistically significant effect of the dimensions of administrative empowerment on the organizational effectiveness of workers in banking sector.